HOUSEHOLD DIETARY DIVERSITY AND NUTRITIONAL STATUS AMONG PRESCHOOL CHILDREN IN EARLY CHILDHOOD INSTITUTIONS - Prasetyaningrum, Yunita Indah; Puspaningtyas, Desty Ervira; Sucipto, Adi; Fitriana, Lala Budi; Rahayu, Andi; Febriyanita, Anggun (Darussalam Nutrition Journal, 2024)
Background: Nutrition problems in preschool children (underweight, stunted, overweight) are a concern in Indonesiamay impact family food intake, especially for children under five years. Low dietary diversity is associated with an increased likelihood of double-burden malnutrition. Objective: This study aimed to determine the relationship between household dietary diversity and the nutritional status of preschool children in Allifa’s Early Childhood Institution. Method: This research was an observational study with a cross-sectional design. The sampling method was purposive sampling in 85 families with preschool children. Household dietary diversity was measured by the Household Dietary Diversity Questionnaire (HDDS). Several indices including weight for age Z-score (were used to calculate the nutritional status of preschool children. Family characteristics were measured by interview using a structured questionnaire, which included age, education level, occupation of the head of household, and number of family members. Data were analyzed using Fisher’s exact test. Subjects were 54.1% female and 45.9% male. The mean age of preschool children was 59,13±14,97 months. Results: Most of the children were 4 years old. The proportion of underweight preschoolers was 5.9%, stunted 12.9%, and overweight 15.3%. The median HDDS score was 10.82±1.356. Most subjects had a high household dietary diversity status (92.9%). Household dietary diversity status was not significantly associated with underweight (p=0.657; 95% CI=0.049-4.357), stunted (p=0.318; 95% CI=0.078-1.923), and overweight (p=0.756; 95% CI=0.369-4.234) incidence. Conclusion: household dietary diversity is not associated with nutritional problems in preschool children.  Keywords: Household Dietary Diversity, Nutritional Status, Preschool Children